Letter from Carl Duncan to Patricia Whiting, August 20, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
A brief note from Duncan mentioning the care of Whiting's houseplants and the health of her mother.